Protocol for a pilot randomized controlled trial of a mobile health exercise intervention for older patients with myeloid neoplasms (GO-EXCAP 2). Issue 4 (May 2022) - Loh, Kah Poh; Sanapala, Chandrika; Janelsins, Michelle; Klepin, Heidi D.; Schnall, Rebecca; Culakova, Eva; Sohn, Michael B.; Vertino, Paula; Susiarjo, Martha; Jensen-Battaglia, Marielle; Becker, Michael W.; Liesveld, Jane; et al.
Abstract: Introduction: We have shown the Exercise for Cancer Patients (EXCAP ©® ) exercise program improved physical function and symptoms and reduced inflammatory markers in patients with cancer. However, adherence to exercise was lower in older adults compared to their younger counterparts. We then leveraged a mobile app to deliver EXCAP ©® and adapted the intervention [Geriatric-Oncology (GO)-EXCAP] for older patients with myeloid neoplasms. In this pilot randomized trial, the primary goal is to determine effect sizes. We propose to assess the preliminary efficacy of GO-EXCAP compared to a behavioral placebo control on physical function, patient-reported outcomes (fatigue, mood, and quality of life), and inflammatory markers in 100 patients aged ≥60 years with myeloid neoplasms receiving outpatient chemotherapy. Methods: GO-EXCAP consists of the EXCAP ©® exercise prescription (daily home-based progressive aerobic walking and resistance exercises with rated perceived exercise of 5–8), EXCAP ©® kit (i.e., activity tracker, resistance bands, print manual, bag), a mobile app, and an in-person or virtual session with the exercise physiologist to deliver exercise prescription. The intervention will last for three cycles of chemotherapy (approximately 12 weeks). The primary outcome measure will be physical function (Short Physical Performance Battery). Secondary outcome measures include fatigue (Brief Fatigue Inventory), mood (Center for Epidemiologic Studies Depression Scale), and quality of life (Functional Assessment of Cancer Therapy-Leukemia). Exploratory outcome measures include inflammatory markers. Discussion: Older adults with myeloid neoplasms receiving outpatient chemotherapy serve as an ideal model for studying an individually tailored mobile health exercise intervention in vulnerable older patients receiving cancer treatments to prevent physical function decline and improve symptoms.